17.6% Conversion Efficiency Multicrystalline Silicon Solar Cells Using the Reactive Ion Etching with the Damage Removal Etching - Ji-Myung Shim; Hyun-Woo Lee; Kyeong-Yeon Cho; Jae-Keun Seo; Ji-Soo Kim; Eun-Joo Lee; Jun-Young Choi; Dong-Joon Oh; Jeong-Eun Shin; Ji-Sun Kim; Ji-Hyun Kong; Soo-Hong Lee; et al. (International Journal of Photoenergy)
For lower reflectance, we applied a maskless plasma texturing technique using reactive ion etching (RIE) on acidic-textured multicrystalline silicon (mc-Si) wafer. RIE texturing had a deep and narrow textured surface and showed excellent low reflectance. Due to plasma-induced damage, unless the RIE-textured surfaces have the proper damage removal etching (DRE), they have a drop in V oc and FF. RIE texturing with a proper DRE had sufficiently higher short circuit current (Isc) than acidic-textured samples without a drop in open circuit voltage (V oc ). And in order to improve efficiency of mc-Si solar cell, we applied RIE texturing with optimized DRE condition to selective emitter structure. In comparison with the acidic-textured solar cells, RIE-textured solar cells have above 200 mA absolute gain in Isc. And optimized RIE samples with a DRE by HNO3/HF mixture showed 17.6% conversion efficiency, which were made using an industrial screen printing process with selective emitter structure.